Plasma C-C Chemokine Concentrations in Intermediate Age-Related Macular Degeneration - Palestine, Alan G.; Wagner, Brandie D.; Patnaik, Jennifer L.; Baldermann, Rebecca; Mathias, Marc T.; Mandava, Naresh; Lynch, Anne M. (Frontiers in Medicine, 2021)
Purpose: To determine the relationship between plasma concentrations of the C-C chemokines CCL2, CCL3, CCL4 and CCL5 and intermediate age-related macular degeneration (iAMD) patients compared with control inidividuals to further define the inflammatory pathways associated with age-related macular degeneration. Methods: The concentrations of CCL2, CCL3, CCL4 and CCL5 were measured using multiplex assays in plasma collected from 210 patients with iAMD and 102 control individuals with no macular degeneration as defined by multi-modal imaging. Non-inflammatory data included in the analysis were: age, sex, family history of AMD, history of smoking, body mass index, presence of reticular pseudo-drusen and cardiovascular disease. Median concentrations as well as a cutoff value for each chemokine were compared between the two groups. Results: The median concentrations of CCL2 and CCL4 did not differ between control and iAMD groups, however, CCL2 was elevated in iAMD when a cutoff comparison was used (p<0.05). Median CCL3 and CCL5 concentrations were significantly decreased in the macular degeneration group compared with controls (p<0.001) as well as when a cutoff value comparison was used. CCL3 and CCL5 were negatively correlated in cases and positively correlated in controls. Conclusions: Plasma CCL3 and CCL5 concentrations were significantly decreased and CCL2 concentrations were increased in patients with iAMD compared with controls, suggesting a role for C-C chemokines in the systemic inflammatory processes associated with disease development.